Inter-Generational Bonding Through Sensory Play: A Conceptual and Empirical Exploration of Attachment and Emotional Co-Regulation (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
With the progressive breakdown of communal living arrangements, loneliness has surfaced as a critical issue affecting aging adults and early-years youth alike. Consequently, cross-generational initiatives have gained traction as potential remedies. Yet, existing scholarly works predominantly evaluate the end results of such initiatives, frequently overlooking the specific underlying processes that forge profound interpersonal ties. This paper proposes a theoretical framework identifying sensory play activities stimulating touch, sight, sound, and proprioception as a primary vehicle for fostering secure attachment and emotional co-regulation between unrelated generations. Drawing upon the foundational principles of Bowlby’s (1969) attachment paradigms and Porges’ (2011) polyvagal insights into interpersonal activation, this manuscript contends that tactile and experiential activities successfully circumvent the communication obstacles frequently observed in mixed-age pairings, particularly those involving toddlers and adults with cognitive decline. We posit that the shared, non-verbal nature of sensory exploration creates a ”safe container” for emotional synchronization. To validate this framework, a pilot study was conducted with 50 participants (N = 50) involved in a structured sensory play intervention. Statistical analysis using SPSS revealed significant correlations between sensory engagement frequency and reductions in state anxiety (r = −.62, p < .01). Furthermore, regression analysis indicated that sensory co-regulation significantly predicts perceived bonding (R2 = .5). The findings suggest that shifting focus from structured tasks to fluid, sensory-based experiences can deepen relational bonds and improve psychological well-being across the lifespan.